Problem nadzoru nad rynkiem finansowym w Unii Europejskiej - Mikita, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Financial stability is the common good and every country should aim to achieve it. New trends which we can observe in European financial market i.e. creating of financial conglomerates and cross-border institutions cause a new problem connected with financial supervision. The rule in European market is that every country organizes its own finance supervision - we do not have European system of financial supervision. The problem is supervising of cross-border institutions. The question arises: who should pay for possible crises caused by such institutions? The main aim of the article is the presentation of the problem of financial supervision in Europe and some ideas how to resolve it. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 316-324